Simplify a - {b - [c - (d - e) - f] - g}.
a + b + c - d + e - f + g
a - b + c - d + e - f + g
a + b + c + d + e - f + g
a - b + c - d + e + f - g

a - {b - [c - (d - e) - f] - g} = a - b + c - d + e - f + g

Expert answered|debnjerry|Points 42940|

Question

Asked 1/17/2013 1:37:58 PM

Updated 1/17/2013 8:53:40 PM

1 Answer/Comment

Rating

0

Simplify 5t + (t - 3) - [(7t + 5) - (8 - 3t)].
-4t
4t
-10t
10t

Weegy: (a)-4t is the answer. 5t + (t - 3) - [(7t + 5) - (8 - 3t)] = -4t User:
Using the polynomials Q = 3x2 + 5x - 2, R = 2 - x2, and S = 2x + 5, perform the indicated operation.
Q - [R + S]
2x2 + 3x - 9
4x2 - 3x + 9
2x2 - 3x + 9
4x2 + 3x - 9
Weegy: D. 5x - 4 is the answer. (More)

Question

Updated 1/17/2013 8:50:08 PM

2 Answers/Comments

5t + (t - 3) - [(7t + 5) - (8 - 3t)]

= 5t + t - 3 - (7t + 5 - 8 + 3t)

= 6t - 3 - (10t - 3)

= 6t - 3 - 10t + 3

= -4t

= 5t + t - 3 - (7t + 5 - 8 + 3t)

= 6t - 3 - (10t - 3)

= 6t - 3 - 10t + 3

= -4t

Added 1/17/2013 7:55:37 PM

Q - [R + S]

= 3x^2 + 5x - 2 - [(2 - x^2) + (2x + 5)]

= 3x^2 + 5x - 2 - (- x^2 +2x + 7)

= 3x^2 + 5x - 2 + x^2 - 2x - 7

= 4x^2 + 3x - 9

= 3x^2 + 5x - 2 - [(2 - x^2) + (2x + 5)]

= 3x^2 + 5x - 2 - (- x^2 +2x + 7)

= 3x^2 + 5x - 2 + x^2 - 2x - 7

= 4x^2 + 3x - 9

Added 1/17/2013 8:50:08 PM

17,410,362 questions answered

S

R

L

1

1

P

C

1

P

1

1

L

P

C

P

C

1

P

C

L

P

C

1

P

C

P

C

P

C

L

Points 1899 [Total 26298]| Ratings 4| Comments 1859| Invitations 0|Offline

There are no comments.